The Impact of Creativity in the Growth and Value of Petrochemical Companies Listed on the Stock Markets of the Gulf Cooperation Council Countries "An Analytical Study" - Al-Hejailan, Saad Hammoud (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to study the effect of the relationship between innovation methods represented in “research and development, training, information technology, and advertising” on the growth and value of petrochemical companies listed in the financial markets of the Gulf Cooperation Council countries, as well as the impact of the age and size of the company on this relationship. The study was conducted on a representative sample of 16 companies from the Gulf Cooperation Council countries, and multiple linear regression was used in conducting the statistical analysis based on the E views program.The study concluded with several results, the most important of which are:1- The results showed a statistically significant effect at the level (α ≥ 0.05) of creativity methods represented in “research and development, training, information technology, and advertising” on the value of the companies under study, as well as the presence of this effect for both research and development, and information technology. and advertising” on the growth of these companies, while the results showed that the training is not moral and has no effect on the growth of these companies.2- The results showed an impact of the age and size of the company on the relationship between “research, development and training” and the growth of the companies under study, while the results showed the absence of this effect on the relationship between “information technology and advertising” and the growth of these companies.The study recommended the necessity of consolidating the conviction of the importance of research and development among these companies, by establishing a specialized department in this field in each company, as well as preparing modern programs and evaluating them periodically to ensure their effectiveness, and allocating a percentage of these companies’ revenues to be able to provide innovative products that satisfy consumers. Attention to creative ideas to improve current products and create new products that lead to an increase in growth rates for these companies. The study also recommended the need to pay attention to information technology, training, and advertising to open new markets at the regional and international levels, which contributes to the growth rates of these companies and improve their financial position.
Keywords: creativity growth; petrochemical companies listed in the financial markets; the Gulf Cooperation Council